Peran Pendidikan Agama Islam Dalam Meningkatkan Spiritual Peserta Didik - Pranoto, Ahmad Hadi; Assharofi, Faiz Abdul Majid; Savana, Oseolla; Nisa, Nafidatun; Junaedi, Mahfud (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping and enhancing students' spirituality in the midst of modernisation and globalisation. This research aims to explore how PAI can strengthen students' spiritual awareness and identify effective learning strategies in shaping their character. This research uses the library research method by analysing various related literatures. The findings revealed that a learning approach that integrates cognitive, affective and psychomotor aspects, supported by Islamic values-based extracurricular activities, can strengthen students' spiritual dimension. In addition, the role of teachers as role models, the habituation of worship, and a supportive educational environment are important factors in building students' religious character. However, in practice, there are still obstacles such as the lack of innovation in teaching methods, which can hinder the effectiveness of PAI. Therefore, more innovative learning strategies are needed, including experiential approaches and the utilisation of technology, so that Islamic religious education is increasingly relevant and has a real impact on the lives of students.